2004
DOI: 10.1023/b:johe.0000016719.89848.b1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Low-Income African-American and Caucasian Adults That Are Important in Self-Management of Type 2 Diabetes

Abstract: Incidence of type 2 diabetes has greatly increased in the US, with over 90 percent having type 2. A cross-sectional, self-report survey was conducted for the purpose of assessing characteristics associated with self-management of type 2 diabetes (attitudes, certain behaviors, and perceived knowledge) among low-income Caucasian and African-American adults enrolled in the Food Stamp Nutrition Education Program (FSNEP). At the time of the study, almost 11 percent of FSNEP adult participants (457 individuals) thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…This problem is particularly apparent in low-income groups (Cox et al 2004). There is therefore a need for effective NE that will assist diabetic individuals overcome barriers to dietary self-care.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is particularly apparent in low-income groups (Cox et al 2004). There is therefore a need for effective NE that will assist diabetic individuals overcome barriers to dietary self-care.…”
Section: Problem Statementmentioning
confidence: 99%
“…Individuals of low socioeconomic status are amongst those noted to experience worse long-term diabetes management outcomes (Roper et al 2001;Levetan, Levitt & Bonnici 1997). This is attributed to more barriers to self-care, including limited access to continuous quality health care (Glazier et al 2006;Cox et al 2004). The complications of poorly controlled diabetes pose a serious social and financial burden, especially to those in resourcelimited settings.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The majority sought to balance their dietary habits with some recommendations. This illustrates the widespread difficulty in adhering to dietary recommendations and the discrepancy between diabetes knowledge and self-care practices [64][65][66][67][68][69][70]. It also implies other factors influence dietary behavior.…”
Section: Prevalence Of Dietary Adherencementioning
confidence: 94%
“…Several other researchers also reported that age was inversely associated with poor dietary adherence with no cause inferred due to study design limitations [58,65,66,76]. Irregular meal patterns and lack of consistency of day-to-day carbohydrates intake in conventional diabetes regimens contribute to poor glycaemic control [56,78].…”
Section: Confounder To Dietary Adherencementioning
confidence: 99%
See 1 more Smart Citation